FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN ASET PASCA PEMEKARAN WILAYAH DAN PENGARUHNYA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DI KABUPATEN TAPANULI SELATAN - rudianto Simamora; Abdul Halim (Jurnal Ekonomi Dan Bisnis, 2015)
This study aims to determine the factors that affect the asset management post-expansion area and its effect onthe quality of financial reports of government in South Tapanuli.This study is a qualitative descriptive study,which aims to explore the factors that affect the asset management post-expansion area and its effect on thequality of financial reporting. Data were collected through interviews with the informants, the studydocumentation, as well as observation or triangulation or a mix of all three. Stages of data analysis used includedata reduction, display data, and drawing conclusions or verification in the preparation of a workinghypothesis.The results showed that factors affecting the asset management division of the post in theGovernment of South Tapanuli include: human resources knowledge assets management, proof of ownership ofassets, valuation of assets, leadership commitment, and attitude: lack of awareness and responsibility.Management of assets after the post-expansion area affects the quality of government financial reports.Keywords: Expansion Areas, Asset Management, Quality of Financial Statements